2010
DOI: 10.1111/j.1365-2966.2010.17283.x
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the Riemann problem in the light of a reformulation of the state equation for SPH inviscid ideal flows: a highlight on spiral hydrodynamics in accretion discs

Abstract: In physically inviscid fluid dynamics, ‘shock‐capturing’ methods adopt either an artificial viscosity contribution or an appropriate Riemann‐solver algorithm. These techniques are necessary to solve the strictly hyperbolic Euler equations if flow discontinuities (the Riemann problem) are to be solved. A necessary dissipation is normally used in such cases. An explicit artificial viscosity contribution is normally adopted to smooth out spurious heating and to treat transport phenomena. Such a treatment of invis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, this is not the conclusion of the full story because Lanzafame (2008Lanzafame ( , 2009 showed that a well bound viscous accretion disc structure modelling strongly depends on several conditions: the kinematic of the mass transfer, γ, αSS and so on. For isothermal or for a quasi-isothermal thermodynamics, a disc is structurally bound even for αSS = 0 because numerical dissipation only is enough to produce a disc in shocks events, a result also discussed by Sawada et al (1987); Spruit et al (1987) and, more recently, by Lanzafame (2010a) in its physical sense.…”
Section: The Physical Kinematic Viscosity Coefficientmentioning
confidence: 90%
“…Nevertheless, this is not the conclusion of the full story because Lanzafame (2008Lanzafame ( , 2009 showed that a well bound viscous accretion disc structure modelling strongly depends on several conditions: the kinematic of the mass transfer, γ, αSS and so on. For isothermal or for a quasi-isothermal thermodynamics, a disc is structurally bound even for αSS = 0 because numerical dissipation only is enough to produce a disc in shocks events, a result also discussed by Sawada et al (1987); Spruit et al (1987) and, more recently, by Lanzafame (2010a) in its physical sense.…”
Section: The Physical Kinematic Viscosity Coefficientmentioning
confidence: 90%